Religious Freedom in English Schools: Neoliberal Legality and the Reconfiguration of Choice - Nigel Fancourt (Religions, 2022)
This paper considers how the longstanding liberal principle of freedom of religion in education in England was recontextualised within a marketised system of school choice. First, the potential conflict between the right to freedom of belief and to education is outlined. The notion of neoliberal legalism is explored, first in identifying and defining neoliberalism as a model of regulation by market forces, then in outlining ‘neoliberal legality’, as the manifestation of this approach in law. Next, the paper presents a narrative account of the development in England of the principle of religious freedom in education up to the Education Act 1944. The neoliberal turn is considered, in the 1988 Education Reform Act and subsequent legislation, showing how while the provision remains, religion is effectively one marker of school choice and strategic school selection, rather than purely a fundamental personal freedom. This is discussed in relation to neoliberal recontexualisation of existing law, and the neoliberal governance of religions.